PENYULUHAN PENCEGAHAN DAN PENGOBATAN TUBERKULOSIS PARU DI POLIKLINIK PARU RSUD RADEN MATTAHER JAMBI - Meidianto; Wahyudi, Dicky; Efendy, Makrup; Miranda, Melly (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
Pulmonary tuberculosis is a contagious infectious lung disease caused by Mycobacterium tuberculosis. This disease is one of the health burdens in Indonesia. Its treatment takes a long time and requires a strong commitment in completing the treatment phase. One of the factors that influence the success of treatment and prevention of pulmonary tuberculosis is the level of knowledge of patients and their families. This community service activity was carried out through counseling and hands-on practice on good cough etiquette. There were 26 participants consisting of patients and families of pulmonary tuberculosis patients in the pulmonary polyclinic room of Raden Mattaher Jambi Hospital. This service has been carried out and went well. It is expected that patients and families can implement the knowledge gained in order to increase treatment compliance and prevent further transmission of pulmonary tuberculosis.